2022
DOI: 10.1002/pmic.202100196
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of metformin effects in 3T3‐L1 adipocytes by SILAC‐based quantification

Abstract: Metformin is a common and generally the first medication prescribed for treatment of type 2 diabetes. Its mechanism involves affecting pathways that regulate glucose and lipid metabolism in metabolic cells such as that of muscle and liver cells. In spite of various studies exploring its effects, the proteome changes in adipocytes in response to metformin remains poorly understood. In this study, we performed stable isotope labeling by amino acids in cell culture (SILAC)‐based quantitative proteomic profiling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…We observed that 3T3-L1 adipocytes accumulated lipid drops 5 days after initiation of differentiation; we thus performed protein turnover experiments 10 days after initiation of differentiation (Supplementary Figure 1A). For biological replicates, we employed a SILAC label-swap replication strategy where light SILAC-labeled adipocytes were changed to heavy SILAC containing Arg10 and Lys8 and heavy SILAC-labeled adipocytes were changed to light SILAC containing Arg and Lys for eight different time intervals: 6, 18, 30, 48, 60, 96, 120, and 144 h. This strategy has been shown to improve reproducibility of the experiments and help in the correction of any experimental errors. ,, …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed that 3T3-L1 adipocytes accumulated lipid drops 5 days after initiation of differentiation; we thus performed protein turnover experiments 10 days after initiation of differentiation (Supplementary Figure 1A). For biological replicates, we employed a SILAC label-swap replication strategy where light SILAC-labeled adipocytes were changed to heavy SILAC containing Arg10 and Lys8 and heavy SILAC-labeled adipocytes were changed to light SILAC containing Arg and Lys for eight different time intervals: 6, 18, 30, 48, 60, 96, 120, and 144 h. This strategy has been shown to improve reproducibility of the experiments and help in the correction of any experimental errors. ,, …”
Section: Resultsmentioning
confidence: 99%
“…We employed a SILAC labeling approach to determine protein half-lives from 0 to 144 h in 3T3-L1 adipocytes. To confirm reproducibility of the protein turnover in 3T3-L1 adipocytes, we applied a SILAC label-swap strategy. ,, , It is reported that label-swapping analysis of SILAC cell culture enhances confidence in the quantification and helps in the monitoring of any experimental errors, for example, incomplete labeling of SILAC. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations